Pengaruh Jenis Inokulum Dan Lama Fermentasi Tempe Kedelai Hitam Terhadap Kandungan Asam Folat Dan Absorbsinya Pada Usus Tikus (Sprague dawley) Secara In Vitro - , NOVIAN WELY ASMORO; , Prof. Dr. Mary Astuti, M.S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Folic acid deficiency will increase the risks of megaloblastic anemia, neural tube defects (NTDs), coronary heart diseases and cancers. Raw soybean is one of the richest sources of folic acid. Soaking, boiling, and steaming soybean cause significant loss of folate during tempe preparation, but Rhizopus spp. fermentation has been reported to increase the folic acid content of boiled soybean. The aim of the study was to investigate the effects of tempe inoculum and incubation black soybean tempe on change in folic acid content and absorbtion of folic acid from the everted intestine rat in vitro. The research was conducted in three phases, the first step was making of inoculum tempe from Rhizopus oligosporus NRRL 2710, Rhizopus oryzae TKAA and Rhizopus stolonifer L-153. The second was making tempe from black soybean (Var. Mallika) with variation of fermentation time 0, 24, 36, 48, 60 and 72 hours and analysis to determine the nutrient content and folic acid. The third analysis absorbtion of folic acid in vitromethod with everted intestine rat (SD). Statistical analysis was performed using SPSS, data were analyzed using analysis of variants (ANOVA) at Î± = 5%. If there are real differences were then tested bythe Duncan Multiple Range Test (DMRT) to determine significant differences amongs treatments. Research found indicate that black soybeans (Var. Mallika) have 3,1 mg/kg folic acid content, soaking and boiling soybean caused loss folic acid become 0,1 mg/kg in soybean ready for fermentation. Fermentation of tempe used R. oryzaeTKAA, R. stolonifer L-153 and R. oligosporusNRRL 2710 caused an increase of boiled soybean contains folic acid subsequently 0,9 mg/kg